Prevalence and Correlates of Zinc Deficiency Among Vietnamese Women of Reproductive Age in Ho Chi Minh City: A Single Hospital-Based Survey - Nguyen, Vinh Quang; Lam, Phong Van; Goto, Aya; Nguyen, Tu Van T.; Vuong, Thanh Nhan T.; Nguyen, Tien Minh; Nguyen, Minh Ha; Truong, Anh Tuyet T.; Tran, Truc Phuong T.; Vo, Chien Duc (Frontiers in Global Women's Health, 2021)
Background and Objectives: Zinc is a micronutrient that plays an important role in metabolism, cell growth regulation, and differentiation. Vietnam has many population groups living in poverty. The daily food of Vietnamese people is mainly rice, which contains very little zinc. This cross-sectional study was conducted to determine the prevalence of, and factors related to, zinc deficiency in women of reproductive age. Methods and Study Design: The sample population was non-pregnant women of reproductive age (18–49 years old) who visited Nguyen Tri Phuong Hospital Gynecological Outpatient Clinic. The subjects were interviewed and data on background characteristics, anthropometric measurements, and blood tests (serum zinc concentration, complete blood count, albumin, and ferritin) were collected. Results: The prevalence of zinc deficiency, as defined by the International Zinc Nutrition Consultative Group (IZiNCG), was 85% [61/72; 95% confidence interval (CI) = 74–91%], and the prevalence of severe zinc deficiency was 37% (27/72; 95% CI = 26–50%). There were significant associations of albumin concentration, marital status, and past pregnancy history with severe zinc deficiency. Conclusions: More than three-fourths of Vietnamese women of reproductive age had zinc deficiency at our study site in Ho Chi Minh City. This health issue requires greater attention in order to swiftly promote preventive actions, and further surveillance to confirm our study findings.